Land suitability Assessment Rubber Commodities ( Hevea brasiliensis) In Nias Selatan District Scale 1: 250,000 - Sebayang, Lukas (Jurnal Online Pertanian Tropik, 2024)
South Nias district was the new district developed of Nias district in 2003. South Nias was part of area hit earthquake and tsunami in 2004 and 2005. The district was the producer of rubber which second superiority commodities after coconut. There were 29,125 Ha of rubber area in South Nias (Statistic of Sumatera Utara Province. 2021). This research activity was carried out in 6 subdistricts in Nias Regency in January 2019 - November 2019. Assessment of land suitability was needed in order to know a directions of superiority commodities development area. This assessment was conducted by using ALES (Automated Land Evaluation System). SDPLE (Standard Procedure for Land Evaluation) data was imported to ALES program. Land evaluation result was show in spatial form. This form made by imported tabulation data to GIS (Geographical Information System) form. Suitability land maps (scale 1 : 250.000) present based on each commodities by ArcView program. Keywords : Suitability land; rubber; South Nias